EFFICIENCY EVALUATION OF THE DIVERSIFICATION OF THE ENTERPRISE ACTIVITY IN THE TEMPORARY ACCOMMODATION AND CATERING FIELD - Dmytro Voronets (Izdevnieciba "Baltija Publishing", 2020)
The temporary accommodation and catering field is a highly competitive field that is why companies in this branch of economy have to make strategic decisions concerned with market expansion and diversification. Diversification of the enterprise activity is very complex and comprehensive strategic decision and has to be evaluated and supervised by management of the enterprise. Besides, the implementation of the diversification strategy requires a lot of resources (financial, material, human) which efficiency is important to evaluate and control. In this article it is examined the problem of evaluating the diversification efficiency of temporary accommodation and catering businesses. The essence of diversification of the enterprise activity is revealed and the general characteristic of the field of temporary accommodation and catering is outlined. The author's goal was to specify indicators for evaluating the efficiency of diversification that are developed in latest scientific publications for use in manufacturing enterprises and their adaptation to the services sector, part of which is the temporary accommodation and catering field. On the basis of the researched scientific works the universal system of indicators for estimation of efficiency of diversification of the temporary accommodation and catering enterprise activity is offered. Three key groups of indicators for evaluation are distinguished: financial and economic, manufacturing and technological, market. Formulas for calculating these indicators are given and their nature is described. The aim of this indicators is to demonstrate the quantitative effect of diversification of the enterprise activity in temporary accommodation and catering field. Besides, indicators also can be adapted and used in other service industries.